KOMPETENSI ABSOLUT PENGADILAN TATA USAHA NEGARA DALAM KONTEKS UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Wahyunadi, Yodi Martono (Jurnal Hukum dan Peradilan, 2016)
In the context of Law Number 30 of 2014 concerning Government Administration the competence of administrative court was not only the decision of the Administration but also has the competence to judge the actions of Administration. In addition administrative court also have competence to decide an application for assessment to determine whether there are elements of authority abuse as well as the application for a fictitious positive decision. However to determine the application for approval of a person or body of civil law are not automatically, but must first be tested through administrative courts. The Government's Administration Law regulates the material law and formal law. For the Government's Administration Law should be amended to load any material law and the need for changes to the Administrative Law to accommodate the enforcement of material law.Keywords: administrative court, competence, material law, formal law.